Seizure as the first manifestation of transitional cell carcinoma of the renal pelvis. Issue 7 (14th July 2020) - Moussa, Mohamad; Chakra, Mohamed Abou; Dabboucy, Baraa; Papatsoris, Athanasios G; Fares, Youssef
Abstract: Upper tract urothelial carcinoma (UTUC) is a rare genitourinary entity of the renal pelvis and the ureter characterized by an aggressive behavior. Cisplatin-based chemotherapy is the first-line therapy of metastatic UTUC. However, a large number of patients with metastatic UTUC are considered ineligible for cisplatin. Immunotherapy emerged as a promising treatment in this setting. Brain metastasis from UTUC is unusual, occurring most often in the presence of systemic metastases. Local therapies such as stereotactic radiosurgery, neurosurgical resection and whole-brain radiotherapy (WBRT) remain the main therapeutic options for brain metastasis. We report a case of a 65-year-old male patient presenting with generalized tonic–clonic seizure. Imaging studies confirmed the presence of multiple brain metastasis. During an evaluation for the primary, he was found to be having metastatic UTUC of the renal pelvis. The brain metastases were treated by hippocampal sparing WBRT with minimal neurotoxicity. The primary tumor was treated by pembrolizumab.